2015
DOI: 10.1111/hel.12193
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends in Helicobacter pylori Infection and Atrophic Gastritis Over 40 Years in Japan

Abstract: There has been a progressive and rapid decline in the prevalence of H. pylori infection as well a fall in the rate of progression of gastric atrophy among H. pylori-infected Japanese coincident with the westernization and improvements in economic and hygienic conditions in Japan since World War II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 38 publications
4
102
1
1
Order By: Relevance
“…Note there was a percentage increase of global incidence of gastritis and duodenitis (18.3%) and peptic ulcer diseases (4.8%) between 2005 and 2015 [1]. Although the prevalence of atrophy in the stomach and the incidence of peptic ulcer disease decrease in some countries [2,3], we observe reports that the prevalence of atrophic corpus gastritis and duodenitis is still high. It is about from 5 to 12% for distinct countries and age groups [4][5][6].…”
Section: Introductionmentioning
confidence: 89%
“…Note there was a percentage increase of global incidence of gastritis and duodenitis (18.3%) and peptic ulcer diseases (4.8%) between 2005 and 2015 [1]. Although the prevalence of atrophy in the stomach and the incidence of peptic ulcer disease decrease in some countries [2,3], we observe reports that the prevalence of atrophic corpus gastritis and duodenitis is still high. It is about from 5 to 12% for distinct countries and age groups [4][5][6].…”
Section: Introductionmentioning
confidence: 89%
“…On the other hand, Kamada et al [5] showed a progressive and rapid decline in the prevalence of H. pylori infection. The overall prevalence of H. pylori infection decreased significantly from 74.7% (1970s) to 53% (1990s) and 35.1% (2010s) [5] .…”
Section: The Geographic Significance Of H Pylori Infection Chronic mentioning
confidence: 98%
“…While the prevalence of Helicobacter pylori (H. pylori) has been decreasing [1,2], it remains a critical public health issue. Recently, increasing prevalence of CAM-resistant H. pylori is an emerging problem of public health all over the world as CAM is included in most first-line empiric H. pylori eradication regimens [3,4].…”
Section: Introductionmentioning
confidence: 99%